"Every Thought and Dream a Nightmare": Violence and Trauma Among Formerly Imprisoned Gang Members. (October 2022) - Gaston, Shytierra; Shamserad, Faraneh; Huebner, Beth M.
Persons involved in gangs disproportionately participate in violence, as both victims and perpetrators. However, much remains unknown about the prevalence and consequences of violence exposure among adult gang members, particularly among those who have been incarcerated. We draw on semi-structured interviews with formerly imprisoned gang members to provide a contextualized account of the continuum of violence before, during, and after prison and illuminate the consequences of cumulative violence exposure among an understudied subgroup at greatest risk for violence. Findings show that adult gang members experience frequent and ongoing exposure to serious violence, as both victims and perpetrators, before, during, and after prison, and directly and vicariously. Although direct involvement in violence dissipated after prison, exposure to vicarious victimization was substantial and ongoing. In addition, respondents reported physiological and psychological consequences related to their chronic exposure to violence and trauma, including nightmares, anxiety, fear, anger, and hypervigilance.